(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2019)
Mobile applications act as valuable tools that can be used by entrepreneurs and small and medium enterprises (SMEs) alike to market their products/services and considerably reduce costs of doing business. The government of Kenya has invested billions of shillings in laying of fiber optic cables in Kenya, improving Kenya‘s ICT sector and coming up with projects aimed at promoting the use of technology among businesses and citizens alike. With all of these investments, there are challenges that hinder the use of business mobile applications by SMEs. Although context awareness in mobile applications is gaining recognition among mobile user and developer communities, many design scenarios still do not incorporate required context awareness as one of their primary goals. Although there are strong context awareness frameworks for mobile applications, there is still potential to improve the usability of virtual learning systems. The study established that the concept of context independence including the physical context independence and the logical context independence from the applications and mobile devices provides a graceful solution in the form of a methodological framework for the development of context-aware systems for SMEs in Nakuru Town.